Comparison of fatigue performance of polyethylene pipe grades in the form of extruded and compression molded specimens - Trávníček, Lukáš; Poduška, Jan; Kučera, Jaroslav; Náhlík, Luboš; Hutař, Pavel (Elsevier, 2023)
Due to the very long operational lifetimes (up to 100 years) of polyethylene pipes, there is a strong demand for accelerated testing of pipe materials to experimentally prove the ability of a certain material to achieve such lifetime. Among the accelerated tests of performance, the cracked round bar (CRB) test is the most convenient. The CRB test takes advantage of cyclic loading that is applied on cylindrical specimens with a circumferential notch in the middle. The specimens are usually manufactured from plates produced by compression molding from the investigated material. However, for polyethylene pipe producers, the possibility of making the specimens by extrusion would save time and lower the costs. This study is dealing with the comparison of CRB test, and a new test carried out on notched pipe samples produced by extrusion. The goal is to investigate the possibility of measuring the performance directly on extruded pipe specimens. The comparison is illustrated on experimental results of several polyethylene pipe grades of PE80, PE100 and PE100RC often used for pipe manufacture.

Due to the very long operational lifetimes (up to 100 years) of polyethylene pipes, there is a strong demand for accelerated testing of pipe materials to experimentally prove the ability of a certain material to achieve such lifetime. Among the accelerated tests of performance, the cracked round bar (CRB) test is the most convenient. The CRB test takes advantage of cyclic loading that is applied on cylindrical specimens with a circumferential notch in the middle. The specimens are usually manufactured from plates produced by compression molding from the investigated material. However, for polyethylene pipe producers, the possibility of making the specimens by extrusion would save time and lower the costs. This study is dealing with the comparison of CRB test, and a new test carried out on notched pipe samples produced by extrusion. The goal is to investigate the possibility of measuring the performance directly on extruded pipe specimens. The comparison is illustrated on experimental results of several polyethylene pipe grades of PE80, PE100 and PE100RC often used for pipe manufacture.
Comparison of fatigue performance of polyethylene pipe grades in the form of extruded and compression molded specimens
Keywords: extruded pipe specimens; SCG resistance; polyethylene pipe lifetime; accelerated testing; extruded pipe specimens; SCG resistance; polyethylene pipe lifetime; accelerated testing